Penjadwalan Produksi Flow Shop untuk Meminimalkan Makespan dengan Metode Pour, Pemrograman Dinamis dan Branch and Bound di CV. Bonjor Jaya - Dwi Agustina Kurniawati (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2019)
Scheduling is defined as the process of allocating resources to select a set of tasks within a certain period. CV. Bonjor Jaya implements scheduling with the First Come First Serve (FCFS) system. This study aims to find the sequence combination of products that have a minimum makespan value using the Pour method, Dynamic Programming and Branch and Bound. The Pour method produces a combination of 3-4-2-1 with an makespan value of 89814.59 seconds. Dynamic Programming Method produces a combination of 3-1-2-4 sequence with an makespan value of 90012.03 seconds. The Branch and Bound method produces a sequence combination of 3-4-2-1 and 3-2-4-1 with an makespan value of 89814.59 seconds. Based on the makespan value obtained, the Pour and Branch and Bound methods are the most appropriate method to be applied in the CV. Bonjor Jaya with the difference in makespan value 484.39 faster than the scheduling method applied by the company.